Precontractual Damages as a Result of an Irrevocable Offer – A Resolution Within the CISG - Bruno Zeller; Robert Walters (Nordic Journal of Commercial Law, 2020)
This paper is written in response to the arguments that have been put forward by Anne Rossen, Maria Pedersen, and Thomas Neumann, titled “How far does the dynamic doctrine go? Looking for the basis of precontractual liability in the CISG”. On the backdrop of this paper, it is worth noting that the United Nations Convention on Contracts for the International Sale of Goods (CISG) is one of the most successful international commercial law treaties ever devised. It has been ratified by most of the world's important trading countries and has become a template for the drafting of commercial law treaties. The CISG is considered a self-executing treaty, as it creates a private right of action in federal court under federal law. It provides the default set of rules that govern contracts for the sale of goods between parties located in different Contracting States. In some cases, the CISG also addresses situations in which only one of the parties is located in a Contracting State. This article argues that the CISG can accommodate breaches of precontractual conditions through the same procedure applied to breaches of contract. It is a controversial issue but, nevertheless, it is arguable that the CISG can cover the internal gap via general principles embedded within its four corners. For this reason, this article will look at Article 16(2). In particular, the following issues will be relevant: the revoking of an irrevocable offer; the effects of Article 4; and the effects of Articles 71- 77.